Analisis Struktur Dinding Penahan Tanah Proyek Rehabilitasi Jembatan Rangka Baja Pantai Dona Kabupaten Aceh Tenggara - Harun Harasid; Deni Trianda Pitri; Khairul Anwar (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Retaining wall is a type of turf that is used to prevent soil from collapsing. Standard Penetration Test (SPT) data can be used to calculate the limit bearing capacity. The purpose of this research is to calculate the limit bearing capacity, to analyze retaining walls and soil stability and to calculate the depth of the pile foundation of retaining walls. This type of research method is quantitative and qualitative research. The research results were obtained based on the soil structure profile of the SPT test results for foundation depth, in which the relative density level of the sand layer can be known, namely N: 0–4 very loose. N :4–10 Release. N : 10–30 Moderate. N : 30–50 Solid. N :>50 Very Dense. And the relative density level of the clay layer can be known, namely N : 0–2 Very Soft. N : 2–4 Soft. N : 4–8 Moderate. N : 8–15 Hard/Stiff. M : 15–30 Very Loud. N : >30 Dense: sedimentary soil type consisting of rocky sandy loam (0.00 – 4.80 m). The carrying capacity using the targazhi method is 29.14 tons. Using the Mayerhof method of 184.45 tonnes. For the soil type of this steel bridge project, the penetration depth of the soil foundation is 6.50m.